2012
DOI: 10.1177/1079063211432475
|View full text |Cite
|
Sign up to set email alerts
|

The Sex Offender Treatment Intervention and Progress Scale (SOTIPS)

Abstract: The Sex Offender Treatment Intervention and Progress Scale (SOTIPS) is a 16-item rating scale designed to assess dynamic risk among adult male sex offenders and degree of change at 6-month intervals during treatment. The purpose of the present study was to examine the psychometric properties of the SOTIPS in a construction sample of 759 adult male sex offenders who were under correctional supervision and enrolled in cognitive-behavioral community treatment in Vermont between 2001 and 2007. The scale showed acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
97
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(102 citation statements)
references
References 36 publications
4
97
1
Order By: Relevance
“…Some of these external factors could be available to evaluators at time of release, such as response to institutional treatment (Olver et al, 2018), or the density of psychologically meaningful risk factors (e.g., Thornton & Knight, 2015). Other variables can only be known after release, such as the quality of their psychological and community adjustment (McGrath, Lasher, & Cumming, 2012) and the receipt of effective community supervision (Duwe & Freske, 2012; Seto, Sandler, & Freeman, 2017). Consequently, evaluators need to consider the empirical risk estimates presented in this article as part of an overall evaluation of risk.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these external factors could be available to evaluators at time of release, such as response to institutional treatment (Olver et al, 2018), or the density of psychologically meaningful risk factors (e.g., Thornton & Knight, 2015). Other variables can only be known after release, such as the quality of their psychological and community adjustment (McGrath, Lasher, & Cumming, 2012) and the receipt of effective community supervision (Duwe & Freske, 2012; Seto, Sandler, & Freeman, 2017). Consequently, evaluators need to consider the empirical risk estimates presented in this article as part of an overall evaluation of risk.…”
Section: Discussionmentioning
confidence: 99%
“…Several third-generation risk tools have been developed for general offenders (e.g., Level of Service/Case Management Inventory, Andrews, Bonta, & Wormith, 2008;OAsys, Howard, 2009); only recently, however, has research focused on third-generation instruments for sexual offenders. Examples of structured risk tools for sexual offenders that meaningfully sample criminogenic needs include STABLE-2007/ ACUTE-2007(Hanson, Harris, Scott, & Helmus, 2007; Structured Risk Assessment (Thornton, 2002a) and its variant, the Structured Assessment of Risk and Need (Webster et al, 2006); the Violence Risk Scale-Sex Offender Version (Olver, Wong, Nicholaichuk, & Gordon, 2007); the Sexual-Violence-Risk Management 20 (Boer, Hart, Kropp, & Webster, 1997); and the Sex Offender Treatment Needs and Progress Scale (McGrath & Cumming, 2003). On average, these frameworks show similar levels of predictive accuracy to static risk factor scales and, in most cases, add incremental predictive validity beyond Static-99 (Beech, Friendship, Erikson, & Hanson, 2002;Olver et al, 2007;Thornton, 2002a).…”
Section: Conceptualizing Causal Risk Factorsmentioning
confidence: 99%
“…A meta-analysis by van den Berg and colleagues (2018) found that dynamic tools and dynamic coding protocols predicted recidivism among men convicted of sexual offenses. These measures included, for example, the Risk for Sexual Violence Protocol (Hart et al, 2003), the Structured Risk Assessment–Forensic Version (Thornton & Knight, 2015), the Sex Offender Treatment Intervention and Progress Scale (McGrath, Lasher, & Cumming, 2012), the Violence Risk Scale: Sexual Offender version (VRS-SO; Wong, Olver, Nicholaichuk, & Gordon, 2003), and STABLE-2007 (Hanson, Harris, Scott, & Helmus, 2007), the latter being the measure that was the focus of the current review. Some of the dynamic risk measures reviewed by van den Berg et al (2018) were also demonstrated to be incremental to static factors— k (samples) = 52, N = 13,446.…”
mentioning
confidence: 99%